Regional Economic Outlook, May 2007, Middle East and Central Asia. (Regional Economic Outlook, 2007)
Strong economic performance across the Middle East and Central Asia is examined against the background of high prices for energy and other commodities. Common economic trends are presented, while prospects and policies are reviewed for the coming year in light of the global economic environment. This latest REO includes boxes treating specific regional topics, such as financial sector reforms and integration in Maghreb countries; economic developments in oil-exporting countries in response to changes in petroleum prices; and the growth boom in the Caucasus and Central Asia.